2018
DOI: 10.1021/acsami.8b10197
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Reactivity of Metastable Intermixed Composite n-Al/PTFE by Polydopamine Interfacial Control

Abstract: The metastable intermixed composite (MIC) is one of the most popular research topics in the field of energetic materials (EMs). The goal is to invent EMs with tunable reactivity and desired energy content. However, it is very difficult to tune the reactivity of MIC due to its high reactivity and sensitivity caused by enlarged specific surface area and intimate contact between the oxidizers and fuels. Herein, we demonstrated a facile fabrication method that can be used to control the reactivity between the nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(44 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…Interestingly, fluorine atoms could decompose the inert Al 2 O 3 shell surrounding the Al NPs into AlF 3 products, producing an exothermic surface reaction that promotes the decomposition of the fluorine-containing oxidizers [ 21 , 22 ]. It has been reported that fluorine-containing oxidizers such as polytetrafluoroethylene (PTFE) [ 23 , 24 ], polyvinylidene fluoride (PVDF) [ 25 , 26 , 27 ], perfluorotetradecanoic acid (PFTD) [ 28 , 29 ], perfluoroalkyl acids (PFAA) [ 30 ], and perfluorohexadecanoic acid (PFHD) [ 31 ] are capable of enhancing the ignition and combustion behavior of Al NPs because of pre-ignition reaction (PIR) which occurs prior to the oxidation reaction of the Al core. However, although the effect of PIR on activating reactivity of Al NPs was demonstrated several years ago [ 32 , 33 ], little attention has been paid to the oxidation mechanism of surface-modification Al NPs regulated by the reaction interface Fuel-Oxidizer ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, fluorine atoms could decompose the inert Al 2 O 3 shell surrounding the Al NPs into AlF 3 products, producing an exothermic surface reaction that promotes the decomposition of the fluorine-containing oxidizers [ 21 , 22 ]. It has been reported that fluorine-containing oxidizers such as polytetrafluoroethylene (PTFE) [ 23 , 24 ], polyvinylidene fluoride (PVDF) [ 25 , 26 , 27 ], perfluorotetradecanoic acid (PFTD) [ 28 , 29 ], perfluoroalkyl acids (PFAA) [ 30 ], and perfluorohexadecanoic acid (PFHD) [ 31 ] are capable of enhancing the ignition and combustion behavior of Al NPs because of pre-ignition reaction (PIR) which occurs prior to the oxidation reaction of the Al core. However, although the effect of PIR on activating reactivity of Al NPs was demonstrated several years ago [ 32 , 33 ], little attention has been paid to the oxidation mechanism of surface-modification Al NPs regulated by the reaction interface Fuel-Oxidizer ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive research has been conducted on the application of additives in reactive materials to tune the reactivity of composites. 16,17 He et al 18 utilized a synthesized polydopamine binding layer to adjust the reactivity of nanoscale Al/PTFE, where it was found that the mixture of PTFE and nanoscale Al coated with polydopamine showed increased energy release and reduced sensitivity, and more importantly tunable reactivity. In order to improve the strength and density of materials, metal particles are also very common additives, such as W particles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fluorine‐containing polymers, such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and perfluoropolyether (PFPE), have been adopted in Al‐based energetic materials, and it has been shown that Al 2 O 3 shell can react exothermically with the fluoride gas decomposed from the polymers, thus transferring the “dead weight” to an energetic constituent . In this way, the oxidation efficiency is also improved when compared with pure ANPs with a dense surface oxide shell.…”
Section: Introductionmentioning
confidence: 99%